2018
DOI: 10.15171/hpr.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B and C Infections in Mokolo District Hospital, Northern Cameroon: The Value of a Screening Campaign

Abstract: Background: Infections due to the hepatitis B (HBV) and hepatitis C (HCV) viruses constitute a global public health problem. Although screening of these infections remains a pivotal tool for timely detection and management of carriers, this preventive measure has been neglected in Africa. Objective: The current study determined the prevalence of hepatitis B surface antigen (HBsAg) and anti-HCV as well as their risk factors through a screening campaign organized in a rural setting in northern Cameroon. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Many seroprevalence estimates for viral hepatitis in Africa preferentially use healthcare facility‐based sampling, 9–12 which may be biased towards those more likely to present to care. These studies also may not reflect recent gains in reducing the transmission of viral hepatitis as most cases of hepatitis B and C transmission occur outside the healthcare setting 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Many seroprevalence estimates for viral hepatitis in Africa preferentially use healthcare facility‐based sampling, 9–12 which may be biased towards those more likely to present to care. These studies also may not reflect recent gains in reducing the transmission of viral hepatitis as most cases of hepatitis B and C transmission occur outside the healthcare setting 13 .…”
Section: Introductionmentioning
confidence: 99%
“…HCVAb seroprevalence in Cameroon varies across regions and tribes within the same country. While some studies reported high HCVAb carriage: in the southern 12% [ 34 ], in the western 6.3% [ 35 ], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [ 27 ], 0.6% in the eastern [ 36 ], 0.4% in the western [ 37 ], 4.8% in the Littoral Region [ 38 ], 1.44% in the center region [ 39 ]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [ 40 ], 1.02% in Sudan [ 41 ], 1.2% in Madagascar [ 42 ], 2.4%in Iraq [ 43 ], 3.6% in India [ 44 ], 19.80% in Cairo [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCVAb seroprevalence in Cameroon varies across regions and tribes within the same country. While some studies reported high HCVAb carriage: in the southern 12% [35], in the western6.3% [36], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [37], 0.6% in the eastern [38], 0.4% in the western [39], 4.8% in the Littoral Region [40], 1.44% in the center region [41]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [42], 1.02% in Sudan [43], 1.2% in Madagascar [44], 2.4%in Iraq [45], 3.6% in India [46], 19.80% in Cairo [47].…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 95%
“…This table presents liver impairment according to hepatitis C antibodies carriage (HCVAb) [26]. While several studies in community settings in Cameroon have also found similar women predominance trend [27,28,29,30], contrary results were more or less reported in rural area of foreign countries including Congo [31], Egypt [32],…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 96%